Modeling Cumulative Effects of Climate and Development on Moose, Wolf, and Caribou Populations. Issue 7 (6th August 2021) - Rempel, Robert S.; Carlson, Matthew; Rodgers, Arthur R.; Shuter, Jennifer L.; Farrell, Claire E.; Cairns, Devin; Stelfox, Brad; Hunt, Len M.; Mackereth, Robert W.; Jackson, Janet M.
ABSTRACT: Wildlife models focused solely on a single strong influence (e.g., habitat components, wildlife harvest) are limited in their ability to detect key mechanisms influencing population change. Instead, we propose integrated modeling in the context of cumulative effects assessment using multispecies population dynamics models linked to landscape‐climate simulation at large spatial and temporal scales. We developed an integrated landscape and population simulation model using ALCES Online as the model‐building platform, and the model accounted for key ecological components and relationships among moose ( Alces alces ), grey wolves ( Canis lupus nubilus ), and woodland caribou ( Rangifer tarandus caribou ) in northern Ontario, Canada. We simulated multiple scenarios over 5 decades (beginning 2020) to explore sensitivity to climate change and land use and assessed effects at multiple scales. The magnitude of effect and the relative importance of key factors (climate change, roads, and habitat) differed depending on the scale of assessment. Across the full extent of the study area (654, 311km 2 [ecozonal scale]), the caribou population declined by 26% largely because of climate change and associated predator‐prey response, which led to caribou range recession in the southern part of the study area. At the caribou range scale (108, 378 km 2 ), which focused on 2 herds in the northern part of the study area, climate change led to a 10% decline in the population and development led to an additional 7% decline. At the project scale (8, 331 km 2 ), which was focused more narrowly on the landscape surrounding 4 proposed mines, the caribou population declined by 29% largely in response to simulated development. Given that observed caribou population dynamics were sensitive to the cumulative effects of climate change, land use, interspecific interactions, and scale, insights from the analysis might not emerge under a less complex model. Our integrated modeling framework provides valuable support for broader regional assessments, including estimation of risk to caribou and Indigenous food security, and for developing and evaluating potential caribou recovery strategies. © 2021 The Authors. The Journal of Wildlife Management published by Wiley Periodicals LLC on behalf of The Wildlife Society. : Boreal woodland caribou in northern Ontario, Canada, are sensitive to climate change and land use because of direct effects to habitat and indirect effects by way of the moose‐wolf‐caribou system. We present an integrated modeling framework with sufficient complexity to assess multispecies population dynamics across large spatial scales that would provide support for project‐level, range level, and regional assessments and planning, including assessment of risk to caribou sustainability and Indigenous food security and for developing and assessing potential caribou recovery strategies.